Pendampingan Pengolahan Minyak Lantung Menjadi Solar dan Aspal sebagai Media Dakwah dalam Pemberdayaan Masyarakat Desa Lerpak Kecamatan Geger Kabupaten Bangkalan - Ianatussoleh; Masruroh; Luaily, Anjaliatul; Sholeh, Moh (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
The program to assist in the processing of Lantung oil into diesel fuel and asphalt, implemented by KKN Group 02 STAI Darussalam in Lerpak Village, Geger Subdistrict, Bangkalan Regency, aims to optimize the use of local natural resources while promoting the economic empowerment of the village community. Lantung oil, which has traditionally been used in a traditional manner, has great potential to be developed into an economically valuable product through a simple distillation process. The activities were carried out using a participatory and sustainable approach, including internal planning, coordination with the village government and community, technical capacity building through study visits, hands-on oil processing, product testing, socialization, and program evaluation. The results of the activities show that Lantung oil can be processed into several fractions, mainly diesel fuel and asphalt, which can technically be used as diesel engine fuel and road hardening material. Field trials have proven that the product functions well, while socialization activities have increased community knowledge, participation, and awareness of work safety and the economic potential of Lantung oil. In addition, the involvement of BUMDes Lerpak as a marketing partner strengthened the institutional and sustainability aspects of the program. Overall, this activity successfully transformed local knowledge into productive practices with added value and has the potential to be developed as a model for village community empowerment based on local natural resources.